2022
DOI: 10.3389/fgwh.2022.893808
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pre-pregnancy body mass index (BMI) among mothers in Abu Dhabi, the United Arab Emirates

Abstract: Pre-pregnancy obesity is a risk factor for several health problems such as gestational diabetes, preeclampsia, labor induction, postpartum hemorrhage, and neonatal hypoglycemia. Being underweight is a risk factor for fetal growth restriction. Despite the negative impact of abnormal pre-pregnancy body mass index (BMI) (over and underweight) on pregnancy outcomes, a limited amount of studies has been conducted on the prevalence of pre-pregnancy over and underweight and associated factors in the United Arab Emira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, Iversen et al estimated an average gain of 0.62 BMI units after each additional birth [ 21 ]. The authors’ previous published data showed an association between increased parity and weight gain; higher maternal age was associated with overweight and obesity [ 22 ]. The combined effects of higher maternal age and higher parity on overweight and obesity could explain the high prevalence of hypertension and diabetes among grand multipara [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Iversen et al estimated an average gain of 0.62 BMI units after each additional birth [ 21 ]. The authors’ previous published data showed an association between increased parity and weight gain; higher maternal age was associated with overweight and obesity [ 22 ]. The combined effects of higher maternal age and higher parity on overweight and obesity could explain the high prevalence of hypertension and diabetes among grand multipara [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%